Determining of The Onset Early Local Rainy and Dry seasons in Tea Plantation - Zakarias Frans Mores Hukom (Agrologia, 2021)
Efforts to increase the productivity and quality of tea shoots are strongly influenced by local climatic and weather conditions at each plantation location.  The existence of climate change globally causes climate change fluctuations and weather elements in almost all tea plantation locations in the world from year to year. Determination of the local climate at each tea plantation location is important in establishing a stable and sustainable production management program and the quality of tea shoots. The weather parameters used for the determination of the start of the local rainy season (AMH) and the start of the dry season (AMK) at the tea plantation location in Tritis hamlet are the amount of rainfall and basic rainy days determined by the Meteorology, Climatology and Geophysics Agency (BMKG).  Rainfall data and local dasarian days of rain for a period of one year were analyzed using subjective descriptive methods involving graphical analysis and spatial analysis. The results showed that the beginning of the rainy season (AMH) in Tritis tea plantation was included in scenario 4 where AMH occurred in October 3 with the amount of rainfall ˃ 50 mm and the number of rainy days ˃ 6 days while the beginning of the dry season occurred in May 2 with the amount of rainfall ˂ 50 mm and the number of rainy days ˂ 6 days.Key words:  AMH, AMK, Rainfall, Dasarian, Rainy Day, and Tea Plantation.